2016
DOI: 10.1126/science.aad8137
|View full text |Cite
|
Sign up to set email alerts
|

Ribose and related sugars from ultraviolet irradiation of interstellar ice analogs

Abstract: Ribose is the central molecular subunit in RNA, but the prebiotic origin of ribose remains unknown. We observed the formation of substantial quantities of ribose and a diversity of structurally related sugar molecules such as arabinose, xylose, and lyxose in the room-temperature organic residues of photo-processed interstellar ice analogs initially composed of H2O, CH3OH, and NH3 Our results suggest that the generation of numerous sugar molecules, including the aldopentose ribose, may be possible from photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
232
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(246 citation statements)
references
References 42 publications
14
232
0
Order By: Relevance
“…Recent analysis of a suite of soluble compounds from CR meteorites led researchers to conclude that a fraction of the compounds (including sugar alcohols) were formed before any possible onset of aqueous alteration in the parent bodies and could therefore have origins in preaccretion environments: Some of the meteorites showed little or no evidence of the action of liquid water (12). Consistent with these findings, recent laboratory experiments designed to simulate the low-temperature irradiation of organic precursors on interstellar grains produced a suite of larger polyols, including multiple sugars (35,36). In the case of formaldehyde, a precursor to polyols, simulations using IR detection have shown that formaldehyde/NH 3 /H 2 O mixtures start to form compounds down to at least 40 K, i.e., temperatures relevant to interstellar/presolar grains (37).…”
Section: Resultssupporting
confidence: 58%
“…Recent analysis of a suite of soluble compounds from CR meteorites led researchers to conclude that a fraction of the compounds (including sugar alcohols) were formed before any possible onset of aqueous alteration in the parent bodies and could therefore have origins in preaccretion environments: Some of the meteorites showed little or no evidence of the action of liquid water (12). Consistent with these findings, recent laboratory experiments designed to simulate the low-temperature irradiation of organic precursors on interstellar grains produced a suite of larger polyols, including multiple sugars (35,36). In the case of formaldehyde, a precursor to polyols, simulations using IR detection have shown that formaldehyde/NH 3 /H 2 O mixtures start to form compounds down to at least 40 K, i.e., temperatures relevant to interstellar/presolar grains (37).…”
Section: Resultssupporting
confidence: 58%
“…[1][2][3][4][5][6][7]13,[15][16][17][18][19][20][21] A separate synthesis of pure glycolaldehyde (2a) and glyceraldehyde (2b) is ostensively implausible, therefore a means of physical separation is better suited to promote the desired selective and sequential delivery of these simple sugars. 6,14,28 Our attention was first drawn to the possible role of 2-aminothiazole (7) in mediating the sequestration, separation and accumulation of glycolaldehyde (2a) and glyceraldehyde (2b) when we observed precipitation of glycolaldehyde (2a) and homochiral D-glyceraldehyde (D-2b) from water as aminals 8a and D-8b.…”
Section: Resultsmentioning
confidence: 99%
“…Schematic of the experimental set-up from Briani et al 2013 of ribonucleotides in a particularly primitive Earth-like environment (Powner et al 2009), were found (de Marcellus et al 2015). More recently, the detection of the aldopentose ribose together with a full family of structurally related sugar molecules have been reported in quite high abundances in the same laboratory ices (Meinert et al 2016). One may also note that nucleobases are suspected to be present in the residue.…”
Section: Interstellar and Cometary Organic Chemistry Simulation Facilmentioning
confidence: 99%